PENGARUH LIKUIDITAS, TANGIBILITY, GROWTH OPPORTUNITY, RISIKO BISNIS, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PERUSAHAAN (Studi Empiris pada Perusahaan yang Terdaftar dalam Development Board Sektor Infrastruktur, Ultilitas dan Transportasi Periode 2012 - 2016) - YUNITA, SANTI; SENO AJI, TONY (Jurnal Ilmu Manajemen (JIM), 2018)
The Indonesia Stock Exchange separates trade boards into main boards and development boards aimed at making investors able to differentiate risk factors. In this study used companies listed in development board infrastructure sector, ultilitas and transportation period 2012-2016. The purpose of this research is to know the influence of liquidity, tangibility, growth opportunity, business risk and firm size to companys capital structure. The sample used amounted to 15 companies with purposive sampling method. This study used a causal associative approach using secondary data obtained through documentation. The analysis method used is multiple linear regression analysis. The results of this study indicate that liquidity and business risk have a negative effect on capital structure. Tangibility, growth opportunity, firm size has no effect on capital structure. The recommendation obtained in this study is that companies need to consider the liquidity and business risks in the preparation of the companys capital structure. Keywords: liquidity, tangibility, growth opportunity, business risk, firm size